Research capacity building integrated into PHIT projects: leveraging research and research funding to build national capacity - Bethany L. Hedt-Gauthier; Roma Chilengi; Elizabeth Jackson; Cathy Michel; Manuel Napua; Jackline Odhiambo; Ayaga Bawah; with input from the AHI PHIT Partnership Collaborative (BMC, 2017)
Abstract Background Inadequate research capacity impedes the development of evidence-based health programming in sub-Saharan Africa. However, funding for research capacity building (RCB) is often insufficient and restricted, limiting institutions' ability to address current RCB needs. The Doris Duke Charitable Foundation's African Health Initiative (AHI) funded Population Health Implementation and Training (PHIT) partnership projects in five African countries (Ghana, Mozambique, Rwanda, Tanzania and Zambia) to implement health systems strengthening initiatives inclusive of RCB. Methods Using Cooke's framework for RCB, RCB activity leaders from each country reported on RCB priorities, activities, program metrics, ongoing challenges and solutions. These were synthesized by the authorship team, identifying common challenges and lessons learned. Results For most countries, each of the RCB domains from Cooke's framework was a high priority. In about half of the countries, domain specific activities happened prior to PHIT. During PHIT, specific RCB activities varied across countries. However, all five countries used AHI funding to improve research administrative support and infrastructure, implement research trainings and support mentorship activities and research dissemination. While outcomes data were not systematically collected, countries reported holding 54 research trainings, forming 56 mentor-mentee relationships, training 201 individuals and awarding 22 PhD and Masters-level scholarships. Over the 5 years, 116 manuscripts were developed. Of the 59 manuscripts published in peer-reviewed journals, 29 had national first authors and 18 had national senior authors. Trainees participated in 99 conferences and projects held 37 forums with policy makers to facilitate research translation into policy. Conclusion All five PHIT projects strongly reported an increase in RCB activities and commended the Doris Duke Charitable Foundation for prioritizing RCB, funding RCB at adequate levels and time frames and for allowing flexibility in funding so that each project could implement activities according to their trainees' needs. As a result, many common challenges for RCB, such as adequate resources and local and international institutional support, were not identified as major challenges for these projects. Overall recommendations are for funders to provide adequate and flexible funding for RCB activities and for institutions to offer a spectrum of RCB activities to enable continued growth, provide adequate mentorship for trainees and systematically monitor RCB activities.